Corporate governance w sektorze publicznym - idea czy rzeczywistość - Filipiak, Beata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
This article presents selected problems of corporate governance in public services. The author discusses:- reasons of introducing new public management by public sector,- idea of corporate governance and its scope,- factors of changing in public sector,- barriers of applications this conception by public services. In the end, the postulates of changing in managing of public services are presented. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 15-25